2018
DOI: 10.3835/plantgenome2017.11.0104
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Machine Learning Methods to Genomic Selection in Breeding Wheat for Rust Resistance

Abstract: New methods and algorithms are being developed for predicting untested phenotypes in schemes commonly used in genomic selection (GS). The prediction of disease resistance in GS has its own peculiarities: a) there is consensus about the additive nature of quantitative adult plant resistance (APR) genes, although epistasis has been found in some populations; b) rust resistance requires effective combinations of major and minor genes; and c) disease resistance is commonly measured based on ordinal scales (e.g., s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 79 publications
4
118
0
1
Order By: Relevance
“…In this study, we compared three linear models characterized by two different assumptions with respect to the distribution of variance for marker effects. In GBLUP and KGD-GBLUP all marker effects are shrunk equally, assuming the predicted trait is controlled by many markers with small effect (Goddard et al 2011), whereas BayesCp assumes that the trait is a mixture of distributions with large and small effect markers (Habier et al 2011). Even with different prior assumptions, Figure 1 illustrates the similarity in predictive ability among the three methods for all nutritive traits, with only minor differences (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we compared three linear models characterized by two different assumptions with respect to the distribution of variance for marker effects. In GBLUP and KGD-GBLUP all marker effects are shrunk equally, assuming the predicted trait is controlled by many markers with small effect (Goddard et al 2011), whereas BayesCp assumes that the trait is a mixture of distributions with large and small effect markers (Habier et al 2011). Even with different prior assumptions, Figure 1 illustrates the similarity in predictive ability among the three methods for all nutritive traits, with only minor differences (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Three whole-genome regression methods, with two different prior assumptions regarding the distribution of marker effects, were used for generating GEBVs. The first method was a univariate linear mixed model, called GBLUP (Goddard et al 2011) in which markers effects were assumed to have equal variance. The linear model can be expressed follows:…”
Section: Genomic Prediction Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…ML had also been used in GS, and it might has the best performance in the interpretation of large-scale genomic data [6]. González et al suggested that ML was a valuable alternative to wellknown parametric methods for genomic selection [9]. Montesinos-López et al found that the predictions of the multi-trait deep learning model were very competitive with the Bayesian multitrait and multi-environment model [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to sugarcane's genomic complexity, simplified predictive models involving linear regression cannot capture the unknown nonlinear characteristics present in these datasets 31 , as described for other polyploid species [36][37][38] . To address this issue, machine learning (ML) methodologies represent a promising approach with high accuracy 31,[39][40][41] . Although GS was developed to address the problem of categorizing individuals using different populations, its application in biparental populations is suitable and might be highly efficient due to the significant amount of linkage disequilibrium between loci 42 , which would facilitate the initial cycles of breeding programs.…”
Section: Introductionmentioning
confidence: 99%